Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1519/jpt.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Combined With Resistance Training for Adults Aged 50 Years and Older: A Systematic Review

Abstract: Background and Purpose: Despite Tai Chi and resistance training being recommended as suitable exercise for older adults, there are no systematic reviews synthesizing the effectiveness of a combination of Tai Chi and resistance training on health promotion of older adults. This study aimed to review the existing literature regarding the effect of Tai Chi and resistance training on physical health, mental health, pain, health-related quality of life, and age-related impairment in adults aged 50 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
1
17
0
2
Order By: Relevance
“…Their recommendation is that the more frail and elderly the individual, the more justification there is for adding progressive resistance and balance training to traditional aerobic exercise programs. Qi et al (2020) report that tai chi in combination with resistance training improves physical function and muscle strength in adults aged 50 and older. Of the seven studies these authors researched that combined both tai chi and resistance training, they concluded that long-term use of these techniques resulted in significant improvement in upper and lower muscle strength, balance and mobility.…”
Section: Cognitive Behavioural Therapymentioning
confidence: 99%
“…Their recommendation is that the more frail and elderly the individual, the more justification there is for adding progressive resistance and balance training to traditional aerobic exercise programs. Qi et al (2020) report that tai chi in combination with resistance training improves physical function and muscle strength in adults aged 50 and older. Of the seven studies these authors researched that combined both tai chi and resistance training, they concluded that long-term use of these techniques resulted in significant improvement in upper and lower muscle strength, balance and mobility.…”
Section: Cognitive Behavioural Therapymentioning
confidence: 99%
“…The search identi ed 36,535 unique citations, of which 1,108 were potentially relevant; at this point, the team elected to limit to systematic reviews (Figure 1). A second screen identi ed 337 citations for full-text review, of which 54 were included (Table 1 (22,24,28,51), combined aerobic and resistance exercise (n = 9) (23,29,34,36,44,46,50,63,75), general PA (n = 9) (32,33,35,40,45,49,52,54,66), mind-body exercise (e.g., Tai Chi, yoga, Pilates) (n = 8) (26, 27,35,43,47,55,58,59), dance (n = 5) (31,37,48,57,63), and other (n = 10) (25,34,35,39,42,53,(63)(64)(65)76). Nutritional supplements included protein (n = 4) (69, 72-74), creatine (n = 2) (67, 71), vitamin D (n = 1) (68), or dairy (n = 1) (70).…”
Section: Resultsmentioning
confidence: 99%
“…• Рекомендуется назначение комплекса упражнений (лечебная физкультура) с частотой 2-3 раза в неделю на протяжении минимум 8 недель всем пациентам старше 60 лет с хронической болью с целью уменьшения боли и повышения мобильности [168][169][170][171][172].…”
Section: уровень убедительности рекомендации C (уровень достоверности доказательств 4)unclassified